Free Trade Agreements and Globalisation In the Shadow of Brexit and Trump - Melchior, Arne (Springer International Publishing, 2018)
This book analyses the fast spread of free trade agreements (FTAs) across the globe, their content and their economic impact. In the wake of Brexit and the new protectionism of President Trump, Melchior offers a timely assessment of key issues relating to FTAs. Dividing the world into seven major regions, he analyses world trade, the globalisation of FTAs and their role within and between the regions. Using a new world trade model, he then presents new evidence on the impact of trade agreements, the value of trade, the impact of China's growth and the West's industrial decline, and the role of reciprocity in trade policy. Covering rich and poor countries, commodity exporters and all of the world's regions, he offers new and original insights about a number of pertinent issues facing today's world. Arne Melchior is Senior Research Fellow at the Centre for International Economics and Trade at the Norwegian Institute of International Affairs (NUPI), Norway. His research interests include international trade and trade policy, economic geography, international inequality and global economic development.